2003
DOI: 10.1203/01.pdr.0000065736.69214.20
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Murine Brain Antioxidant Enzymes

Abstract: Reactive oxygen species produced in cells during normal aerobic metabolism have the ability to induce lipid peroxidation and protein oxidation; therefore, their detoxification and elimination are necessary for physiologic cellular activity and survival. The changes in neuronal antioxidant enzymes from fetal life to adulthood have not been fully described. We investigated protein expression, using Western blot analysis, and enzymatic activity of the antioxidant system-copper-zinc superoxide dismutase (SOD), man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 23 publications
8
88
1
Order By: Relevance
“…development (Chen et al, 1999). As the fetus moves from a hypoxic to a relatively hyperoxic environment, accompanying changes in antioxidant enzymes constitute a compensatory mechanism aimed at protecting the newborn from oxidative stress (Khan and Black, 2003). In the present study, MnSOD mRNA was found in chorion, allantois, and amnion as well as extraembryonic tissues including placenta.…”
Section: Organs (A) Ed 185 Cerebrum (B) Ed 145 Ependymal Cells Ofsupporting
confidence: 54%
“…development (Chen et al, 1999). As the fetus moves from a hypoxic to a relatively hyperoxic environment, accompanying changes in antioxidant enzymes constitute a compensatory mechanism aimed at protecting the newborn from oxidative stress (Khan and Black, 2003). In the present study, MnSOD mRNA was found in chorion, allantois, and amnion as well as extraembryonic tissues including placenta.…”
Section: Organs (A) Ed 185 Cerebrum (B) Ed 145 Ependymal Cells Ofsupporting
confidence: 54%
“…Authors (14,18) studying the levels of various antioxidant enzymes and studies on rat embryos and in rabbit fetuses found a gradual increase in the activity of most enzymes. In addition, multiple studies have demonstrated that the genetic susceptibility plays a key role in MM (2,5,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…11,32,33 The deleterious embryonic and fetal effects of ROS, in the absence of maternal toxicity, likely reflects, in part, the low levels of most embryonic antioxidative enzymes and antioxidants. 6,9 On GD 13, among control embryos exposed in utero to the unsupplemented diet, the increased level of DNA oxidation in p53 null embryos, compared with both their þ/À and þ/þ littermates, suggests that endogenous embryonic oxidative stress in the absence of repair of oxidative DNA damage, one role of p53, may contribute to the more rapid onset of postnatal tumorigenesis in this genotype. Loss of only one p53 allele had no measurable effect on embryonic DNA oxidation, suggesting that, at least in the absence of enhanced oxidative stress, DNA repair in the heterozygous littermates is adequate to contribute, in part, to their slower development of postnatal FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%